2020
DOI: 10.3390/cells9051281
|View full text |Cite
|
Sign up to set email alerts
|

YRNAs: New Insights and Potential Novel Approach in Head and Neck Squamous Cell Carcinoma

Abstract: YRNAs are a class of non-coding RNAs that are components of the Ro60 ribonucleoprotein particle and are essential for initiation of DNA replication. Ro60 ribonucleoprotein particle is a target of autoimmune antibodies in patients suffering from systemic lupus erythematosus and Sjögren’s syndrome. Deregulation of YRNAs has been confirmed in many cancer types, but not in head and neck squamous cell carcinoma (HNSCC). The main aim of this study was to determine the biological role of YRNAs in HNSCC, the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(53 citation statements)
references
References 26 publications
0
53
0
Order By: Relevance
“…In our previous study, we demonstrated that in BRAF-mutant metastatic melanoma patients treated with a BRAF inhibitor, a higher expression of Y RNA-1 was associated with worse prognosis [ 58 ]. Furthermore, Guglas et al, based on HNSCC cell lines, patient samples and TCGA data, indicated that Y RNA-1 was significantly down-regulated, while its higher expression was associated with worse patient survival [ 59 ]. More and more data indicate that YRNAs as well as YRNA-derived fragments are important regulators in tumorigenesis, and they have a potential role in diagnostics [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we demonstrated that in BRAF-mutant metastatic melanoma patients treated with a BRAF inhibitor, a higher expression of Y RNA-1 was associated with worse prognosis [ 58 ]. Furthermore, Guglas et al, based on HNSCC cell lines, patient samples and TCGA data, indicated that Y RNA-1 was significantly down-regulated, while its higher expression was associated with worse patient survival [ 59 ]. More and more data indicate that YRNAs as well as YRNA-derived fragments are important regulators in tumorigenesis, and they have a potential role in diagnostics [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was also observed that higher expressions of YRNA1 are associated with longer DFS and OS in HNSCC patients. YRNA1 expression is associated with changes in the expression of many genes involved in carcinogenesis and its high sensitivity and specificity makes it a possible HNSCC biomarker [ 40 ].…”
Section: Cancer-related Yrnas and Ysrnas And Their Potential As Bimentioning
confidence: 99%
“…Particularly interesting and promising conclusions are made taking into account the presence of YRNAs in cancer and their participation in carcinogenesis. At present, YRNAs have been found in seven types of cancer: BCA, ccRCC, PCA, HNSCC, TNBC, NSCLC, glioma, cervical cancer, colon cancer and PDAC [ 1 , 2 , 3 , 20 , 28 , 32 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Among these, YRNAs exhibit some features that make them potentially promising diagnostic tools.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Interestingly, a tumor-type specific pattern of overexpression was reported [ 41 , 42 ]. Recent studies have shown that the expression patterns of YNRA and YRNA-derived small RNAs are altered in several diseases, including coronary artery disease, Sjogren syndrome, and cancer [ 40 , 43 ].…”
Section: Ctrna: Types Biogenesis and Rolesmentioning
confidence: 99%